Pengaruh Customer Trust dan Customer Statisfaction Terhadap Loyalitas Pelanggan Pada Toko Sembako Ranto - Eva Fitria; Novrihan Leily Nasution (Journal of Management and Creative Business, 2024)
This research aims to determine the influence of Customer Trust and Customer Statisfaction on Customer Loyalty at the Ranto Grocery Store. This type of research is associative research. Data collection in this research was carried out using a survey approach with a quantitative descriptive type of research by distributing questionnaires to 87 respondents, while the population used in this research were loyal customers at the Ranto grocery store. Data collection techniques were carried out using interviews, questionnaires and documentation studies. The data analysis tool used in this research uses SPSS (Statistical Product Software Solution). The data analysis techniques in this research are descriptive analysis, multiple linear regression analysis, hypothesis testing using a partial significant test (t test), simultaneous significant test (F test), and testing the coefficient of determination (R2). The research results show that customer trust and customer satisfaction have a positive and significant effect on customer loyalty both simultaneously and partially